Implementation of Product Model, Price, Place, Promotion in Improving Noken Sales (OAP) - Batlajery, Semuel; Alfons, Marlyn E. (Universitas Pendidikan Ganesha, 2021)
This study aims to analyze the Application of Products, Prices, Places, Promotions in Increasing Papua Noken Sales. A qualitative / descriptive or narrative approach in this study. Primary data is direct data from the Noken seller. Secondary data, namely indirect data from informants from brochures, magazines, and others. Data collection techniques: Observation, namely observing the object / place of research. Interviewing is conducting a series of questions and answers to informants who know best about the object of research. The questionnaire contains structured questions to informants. The informants in this study were 5 Yanti Noken and Syria Noken. This study shows that application of Product, Price, Place, Promotion for Noken sales in increasing revenue, models that must be applied: Application of Product Strategy Models, Application of Price Strategy Models, Application of Place Strategy Models, Application of Promotion Strategy Models. The four models must be worked on together because these models are interrelated. In this model, promotion in the midst of the Covid-19 pandemic is the most effective. Promotion that must be done by salespeople, especially through the online social media (Facebook). The seller must be responsible for delivering the order to the customer's place. The implementation of this Promotion Strategy Model must be carried out, in order to increase income, particularly the Merauke buying and selling forum. The price must be affordable according to the pockets of the community, and still listen to government advice to stay at home and keep the distance.